ANALISIS KEBIJAKAN PRE EMPTIVE SELF DEFENCE GEORGE W. BUSH, JR TERHADAP AFGHANISTAN - , Finahliyah Hasan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is concern to one of United States policy relating to the right of selfdefense or well known as Preemptive Self Defense (PESD). According to the U.S. Congress, Preemptive is defined as "taking military action by a state against another nation so as to Prevent or mitigate a Presumed military attack or to use force by that nation acting against the state" (Murdoch, p.27). By this definition, Bush used the "Preemptive" to attack some country like Afghanistan where suspected terrorist was hiding. PESD becomes controversy because its legality under international law particularly in Article 51 of the UN Charter does not set any explicit reference to this action. The academics differently interpret the contents of the chapter, so that some academics legalize preemptive and others regard it as an act that violates international law because it did not fulfill two conditions when the right of defense permissible. The two conditions are there has been an armed attack and the UN Security Council has taken measures in advance. In addition to Article 51 of the UN charter, legitimacy and precedent of preemptive action is also present in customary international law, which this action can be performed under certain conditions if it meets two conditions: necessity and proportionality. The findings of this research are preemptive self-defense by the United States against Afghanistan does not violate international law. It is based on the transformation of various forms of threats and no longer just an attack by the armed forces as well as terrorism, so the rigid interpretation of Article 51 of the UN Charter is no longer adequate. In addition, the policy of the United States meets the elements of necessity and proportionality, which preemptive action is permissible under customary international law.